Exploring Moroccan EFL Teachers’ Emotional Regulation Strategies and Their Impact on Classroom Dynamics - Oussaleh, El-Houssine; Teimi, Cherif (Universitas Muhammadiyah Yogyakarta, 2026)
Background: Emotions play an essential role in challenging situations. However, unnecessary or inappropriate emotional expression can undermine a person’s ability to manage conflicts effectively. Emotion regulation, therefore, involves the processes through which individuals manage their emotional states, including specific emotions, affect, mood, and stress. Objective: This qualitative study aims to examine how Moroccan English as a Foreign Language (MEFL) high school teachers understand and apply emotional regulation (ER) strategies to manage classroom dynamics. It explored the most frequently employed ER strategies among these teachers, the influence of the learning environment on their emotional regulation, and the impact of ER on students’ learning and performance. Methods: Using a qualitative descriptive research design, this study was conducted in the Rabat-Salé-Kénitra region of Morocco with 15 EFL high school teachers. Data were collected through semi-structured interviews, and a conceptual content analysis was employed to analyse the data. Findings: It led to the emergence of various themes and categories, including teachers’ ability to choose and make effective decisions, adapt to specific contexts, balance their attention, reassess situations, and adjust their responses accordingly. These strategies were thoroughly examined and discussed within the framework of Gross’s Model of Emotion Regulation. Conclusions: The study's findings revealed that respondents were well aware of the significant impact that teachers’ emotion regulation has on their pedagogical practices. The results led us to consider several suggestions and recommendations, including the need for further research to examine other aspects of self-regulation and to address its diverse demands in the twenty-first century.